(untitled) (Jurnal Bina Praja, 2019)
The Aceh Special Autonomy Fund, better known as DOKA, was established in 2008. The amount of DOKA increases significantly every year. However, the increase was not followed by an increase in the local economy. As such, there was no significant improvement in the welfare of the people of Aceh. Therefore, this paper seeks to examine the Aceh Special Autonomy Fund’s Management Model. This paper was using qualitative method through FGD, interviews, and documentation. The results of this study showed the need to improve the performance of the Asymmetric Decentralization Policy through Special Autonomy in Aceh Government such as 1) completion of the drafting of implementing regulations; 2) establish a proactive communication and build trust; 3) socialization by the Ministry of Home Affairs related to the Law on Aceh Government (UUPA) in relation to the Law on Oil and Gas, free trade and others; 4) drafting of guidelines in the implementation of special autonomy; 5) facilitates the division of authority between the Aceh Provincial Government and its district/city governments. The recommendation from this study is to list the division of authority of government affairs in detail between the Aceh Provincial Government and its district/city governments, by considering of the characteristics and aspirations of the regions to avoid disputes over authority and overlapping authority.